Accuracy and reproducibility of protein-DNA microarray technology. - Field, S; Udalova, I; Ragoussis, J (2007)
Microarray-based methods for understanding protein-DNA interactions have been developed in the last 6 years due to the need to introduce high-throughput technologies in this field. Protein-DNA microarrays utilise chips upon which a large number of DNA sequences may be printed or synthesised. Any DNA-binding protein may then be interrogated by applying either purified sample or cellular/nuclear extracts, subject to availability of a suitable detection system. Protein is simply added to the microarray slide surface, which is then washed and subjected to at least one further incubation with a labelled molecule which binds specifically to the protein of interest. The signal obtained is proportional to the level of DNA-binding protein bound to each DNA feature, enabling relative affinities to be calculated. Key factors for reproducible and accurate quantification of protein binding are: microarray surface chemistry; length of oligonucleotides; position of the binding site sequence; quality of the protein and antibodies; and hybridisation conditions.